2020
DOI: 10.1002/app.48985
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior of cold‐water fish gelatin gels crosslinked with 1,4‐butanediol diglycidyl ether

Abstract: In this work, chemical crosslinking with 1,4‐butanediol diglycidyl ether (BDDGE) is used as strategy to enhance mechanical performance of fish gelatin (FG) gels in order to meet the properties' range of mammalian gelatin physical gels. Joint analysis of free amino groups, swelling ratio, and total soluble material indicates that crosslinking degree increases with increasing FG concentration and it is favored by a 0.2 BDDGE/FG ratio. Increasing crosslinking degree enhances gel indentation strength and shear mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Collagen can be either processed by acidic or lime-curing treatment to obtain type A and type B gelatin, respectively. When crosslinked, gelatin forms hydrogels that gained success as scaffolds for regenerative medicine [2], wound dressings [3] and drug delivery applications [4], thanks to its availability, intrinsic presence of cell-adhesive motifs (i.e., RGD sequence), in vivo degradability, and versatility [5]. Different fabrication technologies can be selected to produce gelatin hydrogels (e.g., freeze-drying, particulate leaching, emulsion, 3D printing, electrospinning)…”
Section: Introductionmentioning
confidence: 99%
“…Collagen can be either processed by acidic or lime-curing treatment to obtain type A and type B gelatin, respectively. When crosslinked, gelatin forms hydrogels that gained success as scaffolds for regenerative medicine [2], wound dressings [3] and drug delivery applications [4], thanks to its availability, intrinsic presence of cell-adhesive motifs (i.e., RGD sequence), in vivo degradability, and versatility [5]. Different fabrication technologies can be selected to produce gelatin hydrogels (e.g., freeze-drying, particulate leaching, emulsion, 3D printing, electrospinning)…”
Section: Introductionmentioning
confidence: 99%
“…BDDGE is water-soluble and can be used as a bifunctional crosslinker to bind amino acids. It is widely used for the crosslinking of HA and gelatin [ 122 ]. Zeeman et al studied its mechanism by crosslinking sheep skin with BDDGE (Fig.…”
Section: Modificationsmentioning
confidence: 99%
“…In our previous works, we also found that the use of butanediol diglycidyl ether (BDDE) is safe, as the biocompatibility and cell viability did not change with the use of this material [19]. BDDE was also used to crosslink fish-derived gelatin, and the mechanical properties were examined but not as a biologically applicable material [20]. It had also been discovered earlier that BDDE is suitable to crosslink primary amino groups, and it has been used to modify collagen from sheep [21].…”
Section: Introductionmentioning
confidence: 99%